Patron’s Day 2012 (Institutional Knowledge at Singapore Management University, 2012)
Launch of Singapore Management University's Oral History website at Patron's Day 2012. From left to right, SMU Chairman Ho Kwon Ping, Singapore President and SMU Patron Tony Tan and SMU President Arnoud De Meyer. Patron’s Day 2012 was celebrated at the city campus on 13 January 2012.